Questionnaire for assessment of informal caregiver burden: Integrative review (Research, Society and Development, 2021)
Objective: To identify in the literature, the questionnaires for assessing the burden on informal caregivers. Method: Integrative review, conducted in the search strategies: CINAHL, Virtual Health Library, Web of Science and Scopus (Elsevier). Through the following research question: What are the informal caregiver burden assessment questionnaires available in the literature? The RAYYAN® software was used to import the data. Results: 292 works were found in the databases, of these fourteen included the revision. The studies used 44 assessment instruments, which analyzed depression, anxiety, quality of life, among others, elements that are directly or indirectly related to the burden of informal caregivers. The results were presented in the form of a table and the most used questionnaires to assess the burden of the informal caregiver among the 44 identified in the survey. Conclusion: Numerous instruments were identified that indirectly assessed the burden of the informal caregiver, however only six questionnaires aimed at assessing the burden of the informal caregiver.